Brazil’s Landless Rural Workers Movement (MST) in the Digital Front: mystique as performative practice and insurgent form of political struggle - Aguiar, Janecleide Moura De (Revista Brasileira de Estudos da Presença, 2022)
This research gathered theoretical and methodological subsidies to understand the political organization of the Landless Rural Workers Movement (MST), not only through its classic forms of struggle – occupation of land and marches –, but also through the mystique with dramatizations and performances forming this scenario. The performative practices presented during the 6th National Conference (2014) were studied by searching the database available in different repositories on the Internet and using digital ethnography. In general, the resistance spaces created by social movements in their struggle for emancipation in the 21st century were analyzed.